ANALISIS RASIO UNTUK MENILAI KINERJA PEMERINTAH DAERAH (Studi Kasus Pada BPPKAD Kabupaten Cilacap Tahun 2015-2019 - Hakim Hakim; Umi Rosidah (AmaNU: Jurnal Manajemen dan Ekonomi, 2021)
This research is a quantitative study which is tak en from secondary data on financial reports at the Regional Financial and Asset Management Agency (BPPKAD) in Cilacap Regency. This research takes the title: “Ratio Analysis To Assess Local Government Performance Case Study at BPPKAD Cilacap Regency 2015-2019. The purpose of this study is to determine the performance of local governments in terms of effectiveness ratios, efficiency ratios, compatibility ratios, growth ratios and independence ratios. Based on the results of research and data analysis using financial ratio measurement tools, it shows that: (1) Regional Financial Performance of Cilacap Regency when viewed from the Effectiveness Ratio of is classified as Effective, because the average effectiveness is above 100%, namely 106.83%. (2) The financial performance of Cilacap Regency when viewed from the Efficiency Ratio of Regional Finance is already efficient, because the average ratio is less than 100%, namely 0.98%. (3) The Regional Financial Performance of Regency, when viewed from the Harmony Ratio, still allocates a lot of Operational Expenditure rather than Capital Expenditure. (4) The Regional Financial Performance of Cilacap Regency when viewed from the Growth Ratio is classified as positive. (5) Regional Financial Performance of Cilacap Regency when viewed from the Regional Financial Independence Ratio is still classified as Very Low and in the Instructive relationship pattern category